The good fight. Season three [videorecording (DVD)] - King, Robert (Screenwriter); King, Robert (Screenwriter); Toye, Fred, 1967-; Baranski, Christine; Jumbo, Cush; Leslie, Rose, 1987- (Paramount, 2019)
When an attorney loses her entire life savings and is forced out of the firm that she works for as a result of a financial scam, she must start from scratch at a new firm.